Fertility Preservation Strategies in Cancer Patients: A Comprehensive Review - Razik, Michał; Bator, Piotr; Rozwadowska, Patrycja; Ramian, Jan; Rybak, Jakub; Magiera, Barbara; Magiera, Karol; Razik, Wiktor (Journal of Education, Health and Sport, 2024)
Introduction and purpose. Preserving fertility is crucial for cancer patients, aligning with advancements in oncology. As survival rates improve, addressing treatment-related late effects gains importance. Many young patients, aware of therapy toxicity, consider future conception chances, impacting treatment decisions. With a trend toward delayed childbirth and a growing population facing unplanned family planning disruptions, the demand for fertility preservation is expected to rise. This paper provides a brief review of available methods for preserving fertility in cancer patients. State of knowledge. Freezing semen in liquid nitrogen vapor is a standard method for preserving reproductive potential in male cancer patients. Shielding during total-body radiation limits testicular volume reduction, indicating less damage to the germinal epithelium. Hormone suppression treatments are not protective in male cancer patients. Oocyte and embryo cryopreservation are considered secure methods before anticancer treatments, with oocyte cryopreservation being preferred for post-pubertal women. Ovarian tissue cryopreservation remains an alternative method without preliminary treatment, suitable when time is insufficient for ovarian stimulation. Ovarian transposition beyond the intended radiation area, performed laparoscopically, can retain ovarian function. GnRH agonist administration before and during chemotherapy aims to minimize the likelihood of premature ovarian insufficiency. Summary. Advancements in fertility preservation for cancer patients, ranging from traditional cryopreservation to innovative methods like ovarian tissue preservation, highlight a commitment to empowering individuals facing cancer diagnoses. Ongoing research expands possibilities, ensuring a diverse range of strategies that offer tangible and hopeful prospects at the intersection of cancer and reproductive health.